La stabilité de l’OPEP - Nguyen, The-Hiep (Études internationales, 1979)
In the energy field and more specifically in the petroleum sector, several models have been developed with a view to determining long-term price strategies and supply and demand flows without considering the sector in question from an oligopolistic perspective : institutions have been excluded from these models. This study explicitly recognizes the importance of variables often characterized as extra-economic and proposes to examine the degree of OPEC's stability. Among the factors that could negatively influence this stability are bilateral oil agreements, the coalition of consumer countries within the International Energy Agency and rivalry among the members of OPEC. The respective weight of each of these factors has been carefully examined.On the other hand, an oil price indexing formula accepted and respected by all parties concerned would ensure the stability of this organization. However, stability via indexing is unlikely as it is difficult to find a formula acceptable to all parties. It is therefore to be anticipated that the world energy and petroleum situation in the near future will be a function of the policies of the two poles : the United States, the largest consumer, and Saudi Arabia, the largest producer. The functions-objectives of these two countries have also been examined in order to derive a number of specific hypotheses relative to the eventual evolution of the energy and petroleum sector.